Experimental and modelling studies of coal/biomass oxy-fuel combustion in a pilot-scale PF combustor - Jurado Pontes, Nelia (Cranfield University, 2014)
This thesis focuses on enhancing knowledge on co-firing oxy-combustion cycles to boost development of this valuable technology towards the aim of it becoming an integral part of the energy mix. For this goal, the present work has addressed the engineering issues with regards to operating a retrofitted multi-fuel combustor pilot plant, as well as the development of a rate-based simulation model designed using Aspen Plus®. This model can estimate the gas composition and adiabatic flame temperatures achieved in the oxy-combustion process using coal, biomass, and coal-biomass blends. The fuels used for this study have been Daw Mill coal, El Cerrejon coal and cereal co-product. A parametric study has been performed using the pilot-scale 100kWth oxy-combustor at Cranfield University and varying the percentage of recycle flue gas, the type of recycle flue gas (wet or dry), and the excess oxygen supplied to the burner under oxy-firing conditions. Experimental trials using co-firing with air were carried out as well in order to establish the reference cases. From these tests, experimental data on gas composition (including SO3 measurement), temperatures along the rig, heat flux in the radiative zone, ash deposits characterisation (using ESEM/EDX and XRD techniques), carbon in fly ash, and acid dew point in the recycle path (using an electrochemical noise probe), were obtained. It was clearly shown during the three experimental campaigns carried out, that a critical parameter was that of minimising the air ingress into the process as it was shown to change markedly the chemistry inside the oxy-combustor. Finally, part of the experimental data collected (related to gas composition and temperatures) has been used to validate the kinetic simulation model developed in Aspen Plus®. For this validation, a parametric study considering the factor that most affect the oxy-combustion process (the above mentioned excess amount of air ingress) was varied. The model was found to be in a very good agreement with the empirical results regarding the gas composition.
Keywords: Co-firing; SO3; heat flux; ash deposits; Aspen Plus® simulation